PERFIL BIOQUÍMICO MINERAL NO PRÉ-PARTO DE VACAS MESTIÇAS LEITEIRAS COM PUERPÉRIO FISIOLÓGICO (Veterinária Notícias, 2017)
PERFIL BIOQUÍMICO MINERAL NO PRÉ-PARTO DE VACAS MESTIÇAS LEITEIRAS COM PUERPÉRIO FISIOLÓGICO